2018
DOI: 10.1111/jgs.15245
|View full text |Cite
|
Sign up to set email alerts
|

Core Outcome Set for Trials Aimed at Improving the Appropriateness of Polypharmacy in Older People in Primary Care

Abstract: A COS for interventions aiming to improve the appropriateness of polypharmacy for older people in primary care has been developed. Future work will focus on identifying appropriate tools to measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 26 publications
1
98
0
Order By: Relevance
“…It is advisable to establish an interdisciplinary research team, including consumer representation, to ensure the research is relevant to key stakeholders. Where applicable, core outcome sets for trials aimed at improving medicines use in older people should be used . Research Ethics Committee approval should be sought for all intervention studies and for audits or quality improvement projects that will be presented or published.…”
Section: Objectives Of the Servicementioning
confidence: 99%
See 1 more Smart Citation
“…It is advisable to establish an interdisciplinary research team, including consumer representation, to ensure the research is relevant to key stakeholders. Where applicable, core outcome sets for trials aimed at improving medicines use in older people should be used . Research Ethics Committee approval should be sought for all intervention studies and for audits or quality improvement projects that will be presented or published.…”
Section: Objectives Of the Servicementioning
confidence: 99%
“…Where applicable, core outcome sets for trials aimed at improving medicines use in older people should be used. [71][72][73][74] Research Ethics Committee approval should be sought for all intervention studies and for audits or quality improvement projects that will be presented or published.…”
Section: Researchmentioning
confidence: 99%
“…Researchers and clinicians should focus on developing quality tools using systematic and explicit methods. Such tools should be tested in well‐designed clinical trials that are powered to measure meaningful clinical outcomes (e.g., quality of life, mortality, patient function) . Trials should clearly describe their implementation approach to allow for reproducibility of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…16 Lack of clinical outcome data and inconsistency in outcome measurement have also been highlighted as limitations in deprescribing studies. 54,55 A 2018 systematic review evaluating deprescribing interventions in older persons found that few studies measured clinical outcomes and that none were adequately powered to detect differences in clinical outcomes between intervention and control groups. 56 A number of deprescribing tools have been developed in recent years, but they remain largely untested.…”
Section: Implementation Of Toolsmentioning
confidence: 99%
“…Some have suggested that use of a core outcome set (COS) for studies of medication review in older people would reduce the heterogeneity between trials, increase research output that has relevant outcomes and result in more usable data to inform evidence synthesis [42]. Whilst a couple of COSs have recently been developed [43,44], they will only have impact if used consistently in research trials.…”
Section: Implications For Research and Practicementioning
confidence: 99%